2014 IEEE 23rd International Symposium on Industrial Electronics (ISIE) 2014
DOI: 10.1109/isie.2014.6864828
|View full text |Cite
|
Sign up to set email alerts
|

Development of pseudo autonomous wireless sensor monitoring system for water distribution network

Abstract: Water distribution networks require long term autonomous monitoring solutions, integrated, reliable and cost effective data transfer methods. This paper investigates the data delivery infrastructure of water distribution network sensor equipment used for network monitoring and billing of the subscribers. Water distribution network usually apply sensors to measure water flow, pressure and temperature. The main goal is to offer a wireless sensor system architecture comprising simplified and cost effective design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Basic block scheme (see Fig. 2) represents WSN system that collects and transmits data on water consumption and water temperature at the premises, also water flow and pressure values in the water distribution network [25], [27]. Basic data flow consists of the sensor itself, which registers and converts analog water flow and pressure signal values to digital ones, then data are processed into messages and are sent to the gateway (concentrator) using Short Range Devices (SRD) ISM unlicensed telemetry band, frequency of 868 MHz, which is the main object of analysis in this paper.…”
Section: Impact Of Weather Condition On Manet Routing Protocolsmentioning
confidence: 99%
“…Basic block scheme (see Fig. 2) represents WSN system that collects and transmits data on water consumption and water temperature at the premises, also water flow and pressure values in the water distribution network [25], [27]. Basic data flow consists of the sensor itself, which registers and converts analog water flow and pressure signal values to digital ones, then data are processed into messages and are sent to the gateway (concentrator) using Short Range Devices (SRD) ISM unlicensed telemetry band, frequency of 868 MHz, which is the main object of analysis in this paper.…”
Section: Impact Of Weather Condition On Manet Routing Protocolsmentioning
confidence: 99%
“…Authors in [5] showed the use of wireless sensors in water distribution networks and focused on the energy consumption and the consistency of data in wireless communications. Communication is achieved by adding fixed electric routers to the points where meters cannot be reached.…”
Section: Related Workmentioning
confidence: 99%
“…The energy consumption in wireless communication is important. The lifetime of the battery can be calculated according to the equations below [5]:…”
Section: Proposed Algorithm and Sensor Network Structurementioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing demand to implement a mechanism to enhance the effectiveness of existing water quality monitoring methods. Mostly, water quality information gathering uses traditional or manual methods for various reasons ranging from lack of technology capacity, human resources and financial constraints [5][6][7]. These techniques or methodologies are usually accurate and inexpensive, but suffer from various disadvantages like the loss of vital information during transport, limited samples, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%